TiO2/(CdS, CdSe, CdSeS) nanorod heterostructures and photoelectrochemical properties - Luo, Jingshan (2013)
In this work, nanorods of CdS, CdSe, and CdSeS are deposited by chemical vapor deposition on TiO2 nanorod arrays, and the photoelectrochemical (PEC) performance of the heterostructures is studied comprehensively. It is found that nanorods-shaped CdS are superior to nanoparticles as the photosensitizer. The difference in the photosensitizing effect to TiO2 nanorods among CdS, CdSe, and CdSeS alloy nanorods is studied using optical and electrochemical techniques. The energy levels of these heterostructure photoelectrodes are constructed based on X-ray photoelectron spectroscopy (XPS) and diffused reflectance spectra measurements. The current–time profile with chopped light condition, in combination with time-resolved photoluminescence spectroscopy, reveals that the TiO2/CdS electrode has the lowest carrier recombination rate, highest electron injection efficiency, and highest chemical stability. Nevertheless, in terms of the overall PEC performance (photocurrent level and stability), we propose the TiO2/CdSSe electrode is most favorable.